Ansel Adams - Squires, Buddy; Chin, Michael; Else, Jon; Stiers, David Ogden (PBS, 2004)
Few American artists have reached a wider audience or enjoyed more widespread popularity in their own lifetime than Ansel Adams. Ansel Adams had a profound impact on how Americans see the majesty or their continent and helped transform how people think and feel about the meaning of the natural world. A visionary photographer, a pioneer in photographic technique and a crusader for the environment, this portrait of Adams portrays the great artist and ardent environmentalist.
Bildformat 16:9
Orig.: USA 2002
Keywords: Adams, Ansel <1902-1984>; Photographers -- United States -- Biography; USA; Biografie; Biographical television programs; Video recordings for the hearing impaired